Trichomes Characterization of Ornamental Plants Begonia spp (Begoniaceae) - Hakapaa, Adriana; Sinay, Hermalina; Karuwal, Ritha Lusian; Gusmalawati, Dwi (Biosaintifika: Journal of Biology & Biology Education, 2025)
The presence of sharp needle-shaped hairs on the leaf surface of the ornamental begonia plants is recognized as a trichome that has not been widely studied. This research aimed to determine the characteristics of trichomes of Begonia’s leaves in Ambon. The plant material used was the Begonia species that was explored in Ambon and private collections. Identification of plant species, scientific and trade names was carried out by comparison of the sample plants' characteristics with online data and references. Trichome observations were carried out using the whole mount method with 400x magnification using the Optilab camera of the Olympus microscope. Trichome’s shape and type were described based on the obtained pictures, while number and length were the average of 10 fields of view, from 3 replications, and displayed as mean ± standard deviation (mean ± SD).  The 21 Begonia species were collected, and their trichome was characterized. In general, the Begonia’s trichome consists of structure like base, median or body and tip, uniseriate and multiseriate types, needle or cone shape, and glandular or non glandular. The average length of trichomes range from 29.80-233.47 µm.  Based on these results, it can be concluded that the trichomes on the leaves of Begonia ornamental plants in Ambon City have variations in type, shape, number and size. This result is expected to be new information or references for those who interest in developing Begonia species, especially in classifying begonias based on their trichomes characteristics.